2014
DOI: 10.1039/c3ra46971a
|View full text |Cite
|
Sign up to set email alerts
|

Ship in a bottle synthesis of ionic liquids in NaY supercages for CO2 capture

Abstract: CO 2 is the single most important anthropogenic greenhouse gas, contributing $64% to the global radiative forcing. And the rising concentration of CO 2 in the atmosphere will result in global climate change. In this study, 1-alkyl-3-methylimidazolium bromide ionic liquids (ILs) ([C n MIM]Br, n ¼ 4, 6, 8, 10) were ship in a bottle synthesized in NaY zeolite to get [C n MIM]Br@NaY samples and applied for CO 2 capture. These samples were then characterized by elemental analysis, thermal gravimetric analysis (TGA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…16,17 While encouraging results have been realized with the use of bulk ILs, their poor mass/heat transfer characteristics, low surface area, and associated cost make their industrial use challenging. 18,19 In an effort to resolve these issues, a number of studies have been devoted to the preparation and use of supported ILs. Zhao et al found that supporting ether functionalized imidazolium-based ILs on porous silica gel led to a significant improvement of the composites SO 2 adsorption properties compared to the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 While encouraging results have been realized with the use of bulk ILs, their poor mass/heat transfer characteristics, low surface area, and associated cost make their industrial use challenging. 18,19 In an effort to resolve these issues, a number of studies have been devoted to the preparation and use of supported ILs. Zhao et al found that supporting ether functionalized imidazolium-based ILs on porous silica gel led to a significant improvement of the composites SO 2 adsorption properties compared to the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting adsorbent was found to possess superior thermal stability and improved cyclic CO 2 adsorption−desorption performance compared to the bulk ILs. 18 [APMIM]Br-NaY prepared by the same approach was also found to be a suitable material for CO 2 adsorption. It was determined to possess both physisorbed and chemisorbed ILs, while exhibiting suitable cycling stability at 200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficiency of the IL-based porous materials will be evaluated in terms of stability of ILs in porous structures and their efficiency in applications after recycle. To date, several approaches have been reported on the preparation of IL-based and stable porous materials (e.g., zeolite-based structures), including the ship-in-bottle (SIB), 7,8 ionothermal, 1,9 and postimpregnation [1][2][3][4] methods. The SIB approach is rather impressive and has successfully been applied in the syntheses of stable heteropoly acid (HPA) 10 and metal complexes 11,12 in inorganic porous materials, such as silicalite-1, SBA-15, and MCM-41.…”
mentioning
confidence: 99%
“…More importantly, although its loading is very low, the adsorption performance of ionogel PM-5 at ℃ is fairly competitive with newly reported ionogels with high loading up to 10% -50% (Table S2). 30,[37][38][39][40] With gradually further loading IL up to 30%, the adsorption capacities of PM-10, PM-15 and PM-30 inversely lower to 1.03, 0.90, and 0.57 mmol•(g-Ionogel) -1 respectively ( Fig. 7(e, f, and g) and Fig.…”
Section: Allosteric Effects Driven Rapid Co2 Adsorption Of the Nanocomentioning
confidence: 93%
“…10,[25][26][27][28] In order to make full use of the expensive ILs for CO2 capture, an important strategy is to immobilize or load ILs by incorporation into porous solids to obtain composites called "ionogels". [29][30][31][32] Synergistic effect of ionogels are expected to enhance the efficiency of CO2 adsorption basing on the enlarged interface of gas-liquid. 33 It is reported that the room temperature IL show strong interfacial layering at the support.…”
Section: Introductionmentioning
confidence: 99%